Ocular Granulomatous Meningoencephalitis in a French Bulldog - Asymmetric Bilateral Manifestation - Barbosa Momesso, Eric Orlando; Krebs, Carlos Otávio Eggres; Maia Baruffaldi, Cristiane; Silva, Matheus César da; Brittes Rott, Eduardo; Ruschel Marinho, Diane (Acta Scientiae Veterinariae, 2025)
Background: Granulomatous meningoencephalitis (GME) is an acute, progressive inflammatory disease of unknown etiology that presents as lesions in the central nervous system (CNS). There are 3 forms of occurrence: disseminated, focal, and ocular, the latter being more uncommon. The diagnosis is presumptive and is achieved through exclusion of infectious pathologies, analysis of cerebrospinal fluid, imaging tests, and clinical examination. The aim of this study is to report a case of asymmetric bilateral manifestation of ocular GME in a French bulldog, since this is a sporadic presentation of the disease and an important differential to be considered in cases of sudden blindness in dogs. Case: A 2-year-10-month-old male French Bulldog arrived for ophthalmological evaluation presenting exophthalmos, intense chemosis, unresponsive mydriasis, and negative threat response and glare reflex in the left eye, with normal parameters in the right eye. Fundoscopy of the left eye revealed papilledema, with suspected optic neuritis, which was confirmed by ocular ultrasonography. Treatment was started with topical corticosteroids, which improved the chemosis, but the patient did not return for follow-up appointments. Three months after the last completed consultation, the patient returned complaining of blindness in the right eye, and presenting unresponsive mydriasis, and negative threat response and glare reflex. The patient was referred for magnetic resonance imaging (MRI), collection of cerebrospinal fluid (CSF), and analysis. The day after the consultation, the patient presented chemosis in the right eye, similar to the condition previously presented in the left eye. The CSF analysis revealed a sample composed of 80% lymphocytes and 20% typical neutrophils, with an absence of mitotic figures, phagocytic activity, and bacteria, and a density of 1016 and protein value of 0.6 g/L. Clinical signs associated with elevated CSF density and protein values, mixed pleocytosis, negative CSF qPCR tests for infectious neurological diseases, and unremarkable cranial MRI confirmed the presumptive diagnosis of ocular GME. After diagnosis, the patient was referred to a veterinarian specializing in neurology, where he was prescribed dexamethasone TID eye drops for 10 days to combat eye inflammation. Discussion: The ocular form of GME is an uncommon anomaly that affects the optic nerve of young dogs, causing acute blindness. Although several authors and studies report on the manifestations of the focal and disseminated forms of GME, there are few studies on the ocular presentation of the condition. In the case described, the way in which GME presented in the patient differs from what is commonly described in studies, affecting the dog bilaterally, in an asymmetrical manner, with an interval of 3 months between the presentation in one eye and in the contralateral eye, and without presenting other neurological signs. The cause of this pathology is still unknown. Analysis of the CSF, which showed high lymphocyte activity associated with negative qPCR for infectious diseases, indicates an immune-mediated or idiopathic cause. The patient underwent treatment with cytarabine and corticosteroids prescribed by the neurologist, which led to control of the GME, without progression to other areas, the main sequela being blindness caused by optic neuritis resulting from inflammation. Keywords: optic neuritis, blindness, meningoencephalitis, GME, dogs. Título: Meningoencefalite granulomatosa ocular em um Bulldog Francês - manifestação bilateral assimétrica Descritores: neurite óptica, cegueira, meningoencefalite, MEG, cães.